Sensitive radio-frequency measurements of a quantum dot by tuning to perfect impedance matching - Laird, E; Ares, N; Schupp, F; Mavalankar, A; Rogers, G; Briggs, G; Griffiths, J; Jones, G; Farrer, I; Ritchie, D; Smith, C; Cottet, A (American Physical Society, 2016)
Electrical readout of spin qubits requires fast and sensitive measurements, which are hindered by poor impedance matching to the device. We demonstrate perfect impedance matching in a radio-frequency readout circuit, using voltage-tunable varactors to cancel out parasitic capacitances. An optimized capacitance sensitivity of 1.6 aF/√Hz is achieved at a maximum source-drain bias of 170-μV rootmean-square and with a bandwidth of 18 MHz. Coulomb blockade in a quantum-dot is measured in both conductance and capacitance, and the two contributions are found to be proportional as expected from a quasistatic tunneling model. We benchmark our results against the requirements for single-shot qubit readout using quantum capacitance, a goal that has so far been elusive.